2019
DOI: 10.1111/jam.14502
|View full text |Cite
|
Sign up to set email alerts
|

Presence of diverse nitrate‐dependent anaerobic methane oxidizing archaea in sewage sludge

Abstract: Aim The aim of this study was to explore the community diversity and abundance of nitrate‐dependent anaerobic methane oxidizing archaea, Candidatus Methanoperedens nitroreducens, in sewage sludge from wastewater treatment plants. Methods and Results Seasonal sampling of the sewage sludge was carried out from two wastewater treatment plants (WWTPs) located in the northern and southern parts of China. Through amplicon sequencing using our newly designed primers, a large number of Candidatus Methanoperedens nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It has also been reported that Ca. M. nitroreducens was detected in wastewater treatment plants in both northern and southern regions of China ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Ca. M. nitroreducens was detected in wastewater treatment plants in both northern and southern regions of China ( Xu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Archaea were for a long time thought to be synonyms of extreme environments, since many archaeal isolates were obtained from extreme habitats ( Dassarma et al, 2017 ; Belilla et al, 2019 ; Medina Chávez et al, 2019 ). However, this has changed in the last 30 years thanks to the use of culture-dependent and culture-independent techniques, which demonstrated that these microorganisms are also common in non-extreme environments ( Francis et al, 2005 ; Gleeson et al, 2010 ; Xu et al, 2020 ). It has been hypothesized that the higher resistance of archaea compared to bacteria originates in the composition of their membrane, which is composed of glycerol-ether lipids that are more chemically resistant than those found in the bacterial membrane ( De Rosa et al, 1986 ; Albers et al, 2000 ; Konings et al, 2002 ; Koga and Morii, 2007 ).…”
Section: Introductionmentioning
confidence: 99%